2020
DOI: 10.46234/ccdcw2020.101
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Package Warnings for Adult Smoking Cessation — China, 2018

Abstract: What is already known about this topic? After the framework convention on tobacco control (FCTC) came into force, the health warnings on cigarette packaging in the mainland of China had been changed in three rounds. But the warning label is still only pure text and without descriptions of specific health consequences caused by tobacco use. What is added by this report? Although there were two rounds of changes from 2010 to 2018, current health warning label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This discovery is remarkable, especially given the fact that studies have shown that the difference in smoking behaviours and quitting results between men and women is significant [12,13]. Gender differences in smoking cessation success are influenced by social norms, nicotine metabolism rates, and the availability of cessation resources [14,15]. Thus, creating smoking cessation interventions that are adapted to the specific needs and preferences of different demographic groups is the key to the success of these interventions and the reduction of health inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…This discovery is remarkable, especially given the fact that studies have shown that the difference in smoking behaviours and quitting results between men and women is significant [12,13]. Gender differences in smoking cessation success are influenced by social norms, nicotine metabolism rates, and the availability of cessation resources [14,15]. Thus, creating smoking cessation interventions that are adapted to the specific needs and preferences of different demographic groups is the key to the success of these interventions and the reduction of health inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking prevalence among people aged over 15 years has fallen from 22.7% to 17.5% globally. [1] In 2018, the current smoking prevalence of people aged ≥ 15 years was 26.6% in China, [2] and the number of smokers was estimated to be more than 300 million.…”
Section: Tobacco Usementioning
confidence: 99%
“…Multivariate analysis showed that e-cigarette use, having seen the advertisement, promotion and sponsorship of tobacco in the past 30 days, smoking limit in home or workplace, and awareness of the hazard to result in stroke, heart disease, or lung cancer were associated with smoking relapse rate. [8] Tobacco dependence For ever-smokers, tobacco dependence was diagnosed if they had three or more of the following six symptoms or signs (1) craving or a strong desire or urge to use tobacco; (2) a persistent desire or unsuccessful efforts to cut down or control tobacco use; (3) experiencing tobacco withdrawal symptoms after abrupt cessation of tobacco use or reduction in the amount of tobacco used; (4) tolerance, defined as the need for administrative units with valid data were included in the analysis. Among general population, the prevalence of tobacco dependence was 13.1%.…”
Section: Cardiovascular Health and Diseases In China (2022)mentioning
confidence: 99%
See 1 more Smart Citation